Dynamic Modeling of a Vapor Compression Cycle. Issue 20 (2022) - Husmann, Ricus; Aschemann, Harald
Abstract: This paper presents three alternative dynamic models and a corresponding comparison by simulations for a vapor compression cycle. The first model is derived by first principles and uses both the mass and energy balances in finite-volume models of the evaporator and the condenser, whereas the compressor and the expansion-valve are modeled by means of algebraic equations. Assuming vanishing pressure losses along the evaporator and the condenser, a second model description is established. Additionally, a further simplification concerning the inner mass flows, which can be often found in the literature, leads to a third model. Both model variations are compared in simulations with the original model regarding model accuracy and simulation time. It becomes obvious that the second simplification leads to a significantly larger error. Moreover, the achievable increase in simulation speed of the simplified models is shown. Finally, the impact of a varying spatial resolution is discussed.